Identificação molecular dos bivalves da Família Veneridae, Rafinesque, 1815 (Mollusca, Bivalvia) na Zona Costeira Amazônica (Ilha de Upaon-Açu, Maranhão, Brasil) - Sousa, Ana Karolina Ribeiro (2021)
In Brazil, 40 species of the Veneridae family are popularly known as seafood, bergigão, congole, maçinim, chumbinho and sarnambi. The identification of these taxa based only on morphological characters has generated taxonomic uncertainties. In this sense, the present work aimed to molecularly identify the species of sarnambi found in the coastal zone of the Amazon. The DNA Barcoding methodology was applied, in which a fragment of the Citrochrome Oxidase Subunit I (COI) gene is used. The samples were obtained during the period 2018-2019 in areas of beach and mangrove in the four municipalities of the Island of Upaon-Açu, Maranhão, being registered and identified morphologically. DNA was isolated using Promega's Wizard Genomic DNA Purification protocol kit. The isolation and amplification of the gene were performed through PCR using universal primers. The PCR products were sequenced and data analysis was performed using specific software. In the sequencing of 48 samples, fragments of the COI gene were obtained for Anomalocardia flexuosa with 656 bp, Tivela sp with 647 bp and 653 bp for Leukoma sp. The means of intraspecific genetic divergences showed values of 0.63% for A. flexuosa, 0.65% for Tivela sp. and 0.16% for Leukoma sp. The phylogenetic tree grouped the three species in different clades and strongly supported with 100% bootstrap. The divergence percentages showed high values and similarity below 96% in the comparison between Tivela sp. and Tivela mactroides, the closest species available in BOLDSYSTEMS and although they belong to the same clade, they show a differentiation greater than 4.5%, indicating the existence of a new species, for presenting morphological differences and genetic distance of the species T. mactroides. DNA barcoding confirmed the identification of the A. flexuosa sarnambi in synonymy with Anomalocardia brasiliana. The species Leukoma sp was identified molecularly down to the genus level, due to the lack of data for this taxon on the platform. However, its morphological characteristics point to Leukoma pectorina. The sequence of the COI gene of this species has not yet been included in the BOLDSYSTEMS platform, and this study is a pioneer in the molecular characterization of this taxon. Therefore, our approach with DNA barcoding proved to be efficient and showed the occurrence of a new species for the genus Tivela